Pregnancy effects in the bovine oviduct during early embryonic development in vivo: modulation of the microRNA profile in small extracellular vesicles of the oviductal fluid and oviductal epithelial cells - Mazzarella, Rosane (2021)
The oviduct provides the ideal microenvironment for early embryonic development. This environment is formed by the oviductal epithelial cells (OECs) and the oviductal fluid produced by these cells. Among the contents of OF are the small extracellular vesicles (sEVs), which through their content, including microRNAs (miRNAs), can ensure proper cell communication between the mother and the embryo. However, the miRNA profile modulation in sEVs of the oviductal fluid and OECs in pregnant cows is still unknown. Thus, this project aimed to characterize 383 miRNAs in sEVs from the oviductal flushing and OECs in pregnant (pregnant group) compared to non-pregnant cows (non-pregnant group). Our results indicate that the passage of gametes and the embryo presence modulate miRNAs contents of sEVs and OECs. In OF-sEVs, 8 miRNAs (bta-miR-126-5p, bta-miR-129, bta-miR-140, bta-miR-188, bta-miR-219, bta-miR-345-3p, bta-miR-4523 and bta-miR-760-3p) were up-regulated in pregnant and one miRNA (bta-miR-331-5p) was up-regulated in non-pregnant cows. In OECs, 6 miRNAs (bta-miR-133b, bta-miR-205, bta-miR-584, bta-miR-551a, bta-miR-1193 and bta-miR-1225-3p) were up-regulated in non-pregnant and none was up-regulated in pregnant cows. The functional enrichment of miRNAs highlights pathways involved in physiological processes such as inflammation, cell proliferation, and immune response crucial for both the reproductive tract and embryo development. Additionally, we demonstrated the modulation of the transcriptional levels of selected genes in OECs in pregnant cows. These results suggest that embryonic-maternal crosstalk potentially begins during early embryonic development in the oviduct through the modulation of miRNAs in OECs and sEVs in pregnant cows, increasing oviductal receptivity, allowing proper embryo development leading to a successful pregnancy.